2019
DOI: 10.1002/cncr.32681
|View full text |Cite
|
Sign up to set email alerts
|

2b or not 2b? Shoulder function after level 2b neck dissection: A double‐blind randomized controlled clinical trial

Abstract: Background Selective neck dissection (SND) is a mainstay of head and neck cancer treatment. A common sequela is shoulder syndrome from spinal accessory nerve (SAN) trauma. Extensive dissection in neck levels 2 and 5 leads to SAN dysfunction. However, it is not known whether limited level 2 dissection reduces SAN injury. The purpose of this double‐blind randomized controlled trial was to determine whether omitting level 2b dissection would improve shoulder‐related quality of life and function. Methods Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 41 publications
2
33
1
Order By: Relevance
“…A recent randomized-controlled clinical trial has shown that omitting level IIB in elective SND is safe and is accompanied by decreased shoulder function impairment and increased quality of life, while a significant reduction in operating time was also observed. In that study, only one case of laryngeal squamous cell carcinoma was included in the 'not dissected' IIB group (Dziegielewski et al 2019). Similar conclusions were made by a Japanese group who concluded that level IIB dissection in HNSCC was only necessary in cases where preoperative examination revealed multi-level or level IIA metastases or suspected level IIB metastases (Hosokawa et al 2019).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A recent randomized-controlled clinical trial has shown that omitting level IIB in elective SND is safe and is accompanied by decreased shoulder function impairment and increased quality of life, while a significant reduction in operating time was also observed. In that study, only one case of laryngeal squamous cell carcinoma was included in the 'not dissected' IIB group (Dziegielewski et al 2019). Similar conclusions were made by a Japanese group who concluded that level IIB dissection in HNSCC was only necessary in cases where preoperative examination revealed multi-level or level IIA metastases or suspected level IIB metastases (Hosokawa et al 2019).…”
Section: Discussionsupporting
confidence: 65%
“…A recent work suggested that concurrent neck dissection was not associated with increased morbidity in TL procedures (Xiao et al 2019), which leaves the authors of this study in some doubt when recalling the rates of postoperative complications detected in earlier studies mentioned above including a randomized clinical trial (Dziegielewski et al 2019).…”
Section: Discussionmentioning
confidence: 64%
“…We applaud Dziegielewski et al for meticulously collating an arduous trial, pointing out subtle details and generating a high level of evidence supporting the occurrence of shoulder dysfunction in patients undergoing submuscular recess dissections. 1 Although the literature supporting the omission of level 2b is fractionated, 2 to our knowledge studies have failed to provide concrete evidence with regard to oncological safety and long-term shoulder dysfunction in avoiding submuscular recess dissection. 3,4 Studies till date have indicated that there may be functional disability associated with any type of neck dissection.…”
Section: Preservation Of Spinal Accessory and Level 2b-sparing Neck Dmentioning
confidence: 99%
“…Evidence currently is divided regarding the role of the omission of level 2b based on arguable oncological safety. The study by Dziegielewski et al 1 , through an exemplary model, has emphasized the importance of the SAN in improving functional outcomes. However, the results of the study have to be considered in light of a low sample size and multiple anatomical locations of head and neck squamous cell carcinoma.…”
Section: Preservation Of Spinal Accessory and Level 2b-sparing Neck Dmentioning
confidence: 99%
See 1 more Smart Citation